Utility Bills reimbursement from BUCG-ABC JV for the period from Jan to Dec 2020 - Brac University (Brac University, 2023)
This record consists of general correspondence regarding utility bills reimbursement from BUCG-ABC JV for the period from Jan to Dec 2020 of BRAC University new campus project.